2019
DOI: 10.1080/16549716.2019.1623609
|View full text |Cite
|
Sign up to set email alerts
|

The association between cold extremes and neonatal mortality in Swedish Sápmi from 1800 to 1895

Abstract: Background: Studies in which the association between temperature and neonatal mortality (deaths during the first 28 days of life) is tracked over extended periods that cover demographic, economic and epidemiological transitions are quite limited. From previous research about the demographic transition in Swedish Sápmi, we know that infant and child mortality was generally higher among the indigenous (Sami) population compared to non-indigenous populations. Objective: The aim of this study was to analyse the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The non-Sami population showed no clear seasonal pattern in neonatal mortality, yet a higher mortality was found among infants born in January and November [7]. Furthermore, our previous research showed an association between extreme winter temperatures and neonatal mortality between 1800 and 1900, during which time neonatal mortality increased during the cold winter months (monthly mean temperatures below −15 • C) compared to the milder winter months, particularly among the Sami population [6]. We also found a decreased vulnerability in the Sami population during the second half of the century, suggesting improvements in overall living conditions and health outcomes [6].…”
Section: Seasonality Temperature and Neonatal Mortality In Preindustmentioning
confidence: 84%
See 4 more Smart Citations
“…The non-Sami population showed no clear seasonal pattern in neonatal mortality, yet a higher mortality was found among infants born in January and November [7]. Furthermore, our previous research showed an association between extreme winter temperatures and neonatal mortality between 1800 and 1900, during which time neonatal mortality increased during the cold winter months (monthly mean temperatures below −15 • C) compared to the milder winter months, particularly among the Sami population [6]. We also found a decreased vulnerability in the Sami population during the second half of the century, suggesting improvements in overall living conditions and health outcomes [6].…”
Section: Seasonality Temperature and Neonatal Mortality In Preindustmentioning
confidence: 84%
“…In this paper, we studied the association of daily temperature and seasonality with neonatal mortality, covering a sensitive period of an infant's life. Our previous studies, based on monthly mean temperatures, showed that Sami perinatal and neonatal mortality were influenced by extreme cold in the winter, whereas extreme cold winter temperature had no effect on the non-Sami population [6,8].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations